Transitional factors in race walking - Vallance, B. (Australian Institute of Sport, 2009)
Powerpoint from the 1st European Race Walking Conference about the transition from junior to senior level, the relative age effect, the bitrthplace effect and the gap in performance between juniors and seniors in race walking.